Healthy gut microbiota can resolve undernutrition - Hermann, Emmanuel; Foligne, Benoit (HepatoBiliary Surgery and Nutrition; Vol 6, No 2 (April 15, 2017): Hepatobiliary Surgery and Nutrition (Special Focus on Intrahepatic Cholangiocarcinoma: Part II), 2017)
Child’s undernutrition is widely recognized as a major public health issue in many low- and middle-income countries.